The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1002/nbm.4325
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance spectroscopy in the rodent brain: Experts' consensus recommendations

Abstract: In vivo MRS is a non-invasive measurement technique used not only in humans, but also in animal models using high-field magnets. MRS enables the measurement of metabolite concentrations as well as metabolic rates and their modifications in healthy animals and disease models. Such data open the way to a deeper understanding of the underlying biochemistry, related disturbances and mechanisms taking place during or prior to symptoms and tissue changes. In this work, we focus on the main preclinical 1 H, 31 P and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 162 publications
0
20
0
Order By: Relevance
“…We then formed the Experts Working Group on reporting standards for MRS , who support the paper's recommendations with collaborators with more than 5 years of experience in MRS methodology and application, who either have extended years of service as reviewers for the main MRS journals or are editors of those journals. This follows the same pathway to consensus as the other consensus papers in this special issue 6–17 . These consensus papers provide context to these recommendations, and for further details, as indicated throughout the paper, new authors should reference these papers.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…We then formed the Experts Working Group on reporting standards for MRS , who support the paper's recommendations with collaborators with more than 5 years of experience in MRS methodology and application, who either have extended years of service as reviewers for the main MRS journals or are editors of those journals. This follows the same pathway to consensus as the other consensus papers in this special issue 6–17 . These consensus papers provide context to these recommendations, and for further details, as indicated throughout the paper, new authors should reference these papers.…”
Section: Introductionmentioning
confidence: 90%
“…Below we set out in five sections the important pieces of information about an MRS study that are to be considered as either requirements, or recommendations, along with reasons why these are considered important. A more in‐depth description of terminology and abbreviations to be used can be found in the work of Kreis et al, 11 while a fuller discussion of several concepts are to be found in other consensus papers in this special issue 6–17 …”
Section: Reporting Guidelinesmentioning
confidence: 99%
“…For a detailed discussion of those aspects, please refer to the dedicated paper on this subject in this issue of NMR Biomed. 148 …”
Section: Further General Terminologymentioning
confidence: 99%
“…For a detailed discussion of those aspects, please refer to the dedicated paper on this subject in this issue of NMR Biomed. 148 T A B L E 2 (Continued) This report explains terms that describe context, concepts and terminology relevant for in vivo MR spectroscopy, in particular for the description of MRS methods and the properties of in vivo MR spectra. This has emerged as a consensus among a large group of contributing authors who are experts in the field, as documented by their publication histories.…”
Section: Further General Terminologymentioning
confidence: 99%
“…The combination of medetomidine and isoflurane is now currently considered one of the most appropriate anesthetic protocols available for the evaluation of murine functional connectivity [ 36 ]. However, the extent to which different anesthesia protocols impact cerebral metabolism is an important topic that remains to be investigated [ 38 ]. Thus, the second aim was to assess the impact of this two anesthetic conditions on the cerebral metabolism of HP [ 2 H 7 , U- 13 C 6 ] Glc and non-HP [6,6′- 2 H 2 ] Glc detected by X-nuclei MRS.…”
Section: Introductionmentioning
confidence: 99%